Basics English review English the easy way - Schachter, Norman (South-Western Educational Pub, 1999)
This popular English text takes an unique and time proven apporach to teaching the basics of grammar, punctuation, spelling, vocabulary, and writing skills. Designed to be user-friendly, Basic English Review targets users who have traditionally been unmotivated by learning English grammar. Concepts are logically organised, explanations are short and skill practice is abundant so that the once discouraged student gains confidence and skill in these areas.